The factors that influence job performance - Nor Hidayah, Omar (2015)
Job performance is an individual output in terms of quality and quantity expected from every employee in a particular job. Individual performance is most of the determined by motivation and the will and ability to do the job. This study was conducted to find the factors that influence job performance among non-executive employees at Telekom Malaysia Berhad Kedah and Perlis and used quantitative method in determining the relationship between all the independent variables (reward and recognition, training and development and proactive personality) and dependent variable (job performance). This study involved 250 respondents from non-executive employees Kedah and Perlis. Researcher has distributed 300 sets of questionnaire to the respondents but researcher only received back 250 completed questionnaires. The questionnaire contains of 34 items that have used five point Likert scale. Each hypothesis was tested using Statistics Package for Social Science (SPSS) version 20.0. The obtained data were analyzed using descriptive analysis and inferential analysis namely correlation and regression. Three hypotheses were formed after performed the inferential analysis was used to determine the relationship between independent variables and dependent variable. The results of the study showed that that most of the respondents agreed that the two factors which are training and development and proactive personality can increase their job performance. As a conclusion, training and development and proactive personality can give positive effects to the non-executive employees through their good performance. The findings were discussed and recommendations for further research were also addressed